ANALISIS KARAKTER TOKOH UTAMA DALAM NOVELATHE STRANGE CASE OF DR. JEKYLL AND MR. HYDE KARYA ROBERT LOUIS STEVENSON - PANDIANGAN, ROY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â  The research is entitled â€œAnalisis Karakter Utama dalam Novela The Strange Case of Dr. Jekyll and Mr. HydeKarya Robert Louis Stevensonâ€. There are eight characters in this novella but only two major characters, and this analysis focuses on the analysis of major character â€œDr. Jekyllâ€ who is also known as â€œMr. Hydeâ€. The main purpose of this research is to describe the personalityâ€™s: good and bad sides of the major character which is based on theory Robertâ€™s theory. The researcher uses descriptive method and the data are taken from the novella itself. The data are analyzed intrinsically to find out the main characterâ€™s personality. After analyzing the personality of major character the writer finds that Dr. Jekyll Â has both good and bad sides of his personality, and then he tries to make poison, try to separated these two different personalities. Â  Keywords: Major Character, Dr. Jekyll and Mr. Hyde, Good and Bad Personality.